Descriptions of larvae of the tribe Hyperini (Coleoptera: Curculionidae): III. Mature larvae of the genus Donus Jekel, 1865 - Skuhrovec, Jiãí (Zootaxa, 2007)
Descriptions of mature larvae of ten species of the genus Donus Jekel, 1865 are given: larvae of D. austerus (Boheman, 1834); D. cyrtus (Germar, 1821); D. osellai Winkelmann, 2001 and D. reichei (Capiomont, 1868) are described for the first time, larvae of D. comatus (Boheman, 1842); D. oxalidis (Herbst, 1795); D. palumbarius (Germar, 1821) and D. tesselatus (Herbst, 1795) are described for the first time in detail, and larvae of D. crinitus (Boheman, 1834) and D. intermedius (Boheman, 1842) are redescribed. An identification key for the mature larvae of twenty-nine Hyperini-species known so far is presented.